Identification of the BRCA1 Gene Mutations in Exons 6, 13, and 20 in Patients with Breast Cancer, South Khorasan Province, Iran - Ghazaleh Khalili Tanha; Ahmadreza Sebzari; Mitra Moodi; Mohsen Naseri (Mashhad University of Medical Sciences, 2018)
Introduction: Breast cancer is the most prevalent malignancy among females and the first leading cause of death from cancer in women. This highly heterogeneous disease is multifactorial. Mutations in BRCA1 and BRCA2 genes, which contribute to DNA repair, are the causes of 20-30% of hereditary breast cancers. Therefore, this study was conducted to determine the BRCA1 mutations in patient with breast cancer in South Khorasan Province, Iran, during 2015 to 2017. Methods: In this descriptive study, we collected 88 peripheral blood samples from patients with breast cancer, 11 of which had a positive family history of the disease. The BRCA1 gene was amplified in the DNA isolated from female patients using polymerase chain reaction (PCR) technique. Then, the BRCA1 mutations in exons 6, 13, and 20 were analyzed by PCR-single-strand conformation polymorphism (SSCP), silver nitrate staining, and DNA sequencing. Data analysis was performed using SPSS software, version 22. Results: In this study, no mutation was observed in the exons 6 and 20. In addition, a polymorphism was found in the exon 13. This variant (c.4308T>C) was detected in 28 patients, four of them (14.2%) had hereditary breast cancer. The frequency of the mutation was 36.3% and 31.1% in patients with hereditary and non-hereditary, respectively. Conclusion: In this study, BRCA1 gene mutations did not occur in exons 6 and 20. Additionally, a polymorphism rs1060915 in exon 13 of the BRCA1 gene was observed with the frequency of 31.8%.